Effect of Information Technology, Investment Knowledge and Financial Literacy Millennial Generation Of Interest Invest in Capital Market - Apren Halomoan Hutasoit (Institute of Computer Science (IOCS), 2021)
This research was conducted with the intent and purpose is to determine the effect of Information Technology, investment knowledge, and financial literacy to the interest of the millennial generation invests in the stock market. This research is an associative research with a quantitative descriptive approach. This research was conducted in the city of Medan with a sample of 96 people. The model used in this study is multiple linear regression. The results of this study indicate that information technology affect investment interest. Furthermore, investment knowledge also influences investment interest. And lastly, financial literacy affects investment interest. The results of this study indicate that the more advanced the development of technology, the millennial generation increasingly understands financial literacy, and the millennial generation has investment knowledge, the more it will increase their interest in investing in the capital market.